2014
DOI: 10.2147/btt.s57253
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and the FLIP and NF-kappa B proteins as pharmacodynamic criteria for biosimilar TNF-alpha antagonists

Abstract: Various criteria are necessary to assess the efficacy and safety of biological medications in order to grant companies the right to register these medications with the appropriate bodies that regulate their sale. The imminent expiration of the patents on reference biological products which block the cytokine TNF-α (tumor necrosis factor-α) raises the possibility of bringing so-called biosimilars to the market (similar to the biologicals of reference products). This occurrence is inevitable, but criteria to ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Similar to our own results, several studies have concluded that NF-kB levels, which are determined by IHC, have a significant role in nephrotoxicity damage (Yang et al, 2012). Further, infliximab and other TNF-α inhibitors have been shown to reduce NF-kB levels (Urbano et al, 2014). Regarding tissue damage, the existence of a mechanism between TNF-α, TGF-1β, and NF-kB for inducing each other has been identified (Sanchez-Capelo, 2005).…”
Section: Page 12 Of 34supporting
confidence: 84%
“…Similar to our own results, several studies have concluded that NF-kB levels, which are determined by IHC, have a significant role in nephrotoxicity damage (Yang et al, 2012). Further, infliximab and other TNF-α inhibitors have been shown to reduce NF-kB levels (Urbano et al, 2014). Regarding tissue damage, the existence of a mechanism between TNF-α, TGF-1β, and NF-kB for inducing each other has been identified (Sanchez-Capelo, 2005).…”
Section: Page 12 Of 34supporting
confidence: 84%
“…It is important to note that several biologics agents including etanercept will lose patent protection in Europe by 2015, which increased the interest in the development of new biologic agents (Willrich et al 2014); therefore, data regarding the characteristics of action of these drugs are important for the formulation of comparison criteria of the efficacy and safety (Urbano et al 2014). The effects of etanercept on inflammation reported in this paper contribute for a better knowledge of the in vivo action of this drug on inflammation.…”
Section: Discussionmentioning
confidence: 87%
“…Bars indicate the mean±SEM of five animals. *p < 0.05, **p < 0.01 pathway, promoting the reduction of antiapoptotic genes expression in these inflammatory cells (Sabroe et al 2005;Urbano et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The CRS is associated with the binding of IFX to the transmembrane TNF alpha in immune cells that activates a cascade of apoptotic signalling which is observed within few hours from the administration with cell degradation and massive release of cytokines in Rheumatoid Arthritis (RA) and CD patients [8, 21]. A shorter infusion duration may interfere with cytokine release for instance reducing the IFX exposure time needed to activate the apoptosis.…”
Section: Discussionmentioning
confidence: 99%